MUTASI KERJA DALAM SATU GRUP PERUSAHAAN. STUDI KASUS : (PUTUSAN PENGADILAN NEGRI NOMOR 144/PDT.SUS-PHI/2019/PN.PLG DAN PUTUSAN MAHKAMAH AGUNG NO 1283K/PDT.SUS-PHI/2020) - Hubertus Panji Dwi Sabmoko; Gunardi Gunardi (Fakultas Hukum Universitas Tarumanagara, 2021)
Humans in life have many needs that must be met. To achieve these needs, humans can make a business or work. By working people earn income to meet their needs. Manpower according to Article 1 point 2 of Law number 13 of 2003 states: Manpower is anyone who is able to do work to produce goods and or services to meet the needs of themselves and the community. Most of the Indonesian people are workers, therefore the welfare of the workforce and their families has an important role in creating social justice for all Indonesian people. To achieve a just, prosperous and materially or spiritually prosperous society cannot be realized if the workforce and their families do not prosper. Improving the welfare of the workforce and their families is in the context of realizing the welfare of the Indonesian people. Mutation or placement of workers is a common thing in every company. Transfers between companies that are still in one group of companies have not been regulated in Law number 13 of 2003 concerning Manpower.